Faktor-Faktor yang Mempengaruhi Praktik Perataan Laba pada Emiten dalam Industri Manufaktur dan Indeks LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2006-2008 - Witjaksono, Armanto; Tediyanto, Tediyanto (Binus Business Review, 2011)
The purpose of this research was to test factors that influence income smoothing in manufacture industry which listed in Indonesia Stock Exchange (BEI) and in companies registered in LQ45 index. Factors would be tested were company size, profitability, financial risk, and public ownership structure. Number of sample was 74 companies consist of 65 manufactures and 9 other registered in LQ45 respectively. Sample selection conducted using purposive sampling method. The criteriaâs were the companies should been listed from year 2006 until 2008, never reporting net loss, complete data, reporting currency was IDR, did not involve in any merger nor acquit ion, and consistently registered in LQ45 index during observation. To identify the company that conduct income smoothing we using Eckel Index. Hypothesis would be tested using binary logistic regression. The results showed that company size had significant influence toward income smoothing, however profitability, profitability, financial risk, and public ownership structure had not significant influence toward income smoothing.Â